A Priest’s Drama: Between a Calling and a Metaphysical Revolt (Vincas Mykolaitis-Putinas’ In the Shadows of Altars and Georges Bernanos’ Under Satan’s Sun) - Bikulčius, Vytautas (Literatūra, 2018)
[full article and abstract in Lithuanian; abstract in English]The paper deals with the influence of the Catholic revival (le renouveau catholique) in France on Vincas Mykolaitis-Putinas’ novel In the Shadows of Altars. The novel is a natural continuation of Lithuanian literature. It is no coincidence that the author, while primarily focusing on the psychological side of the novel’s protagonist, at the same time demonstrates the tradition of the classic (the Balzacian or the Stendhalian) novel. When Liudas Vasaris begins his studies at the Theological Seminary he realizes that a calling to serve God is his life problem – there is a clash between the priesthood and his ambition to be a poet. But he is not likely to rebel against God as he does not perceive the priesthood to be his own life’s path. Thus, the priesthood does not become Liudas Vasaris’ existential experience, he confines himself to the earthly milieu. In this way Liudas Vasaris differs from the protagonist of George Bernanos’ novel Under Satan’s Sun, Father Donissan, who dares to rise above earthly life and stand up to God and perceive it as a metaphysical revolt. Mykolaitis-Putinas, who probably knew Bernanos’ novel, most likely saw it as an additional material that demonstrates a priest’s path.
Keywords: Catholic revival in literature; Vincas Mykolaitis-Putinas; Georges Bernanos; psychological novel; priesthood; problem of calling; metaphysical revolt